Information Technology and Human Resources Function Performance in The COVID 19 Pandemic Context: Case of Public Higher Education Establishments of UH2C - Youssef DHIBA; Ghizlane DIAB; Khalid LAHYANI (Communications of International Proceedings, 2021)
Taking into account the globally dynamic and unpredictable context, organizations are increasingly using information and communication technologies (IT) to develop the human resources function HRF and make it capable of responding to the complexity and the diversity of demands of the human component. But despite all the efforts made to set up management tools, human resources managers still observe a weakness in relation to the degree of impact of digital technology on HRF performance. This research article is based on an empirical study carried out in the context of the COVID 19 pandemic, and concerns public higher education institutions under the Hassan II University of Casablanca. in this context. We are developing the results of this study with the objective of assessing the impact of IT on the performance of the HRF, while taking into account the human component, considered as a key factor in the successful implementation of information technology.
Keywords: Technologies of Information and of Communication; Human Resources Function; Information System of HR; performance of HRF.